Direct pulmonary infiltrates as an initial manifestation of chronic lymphocytic leukemia. (2018) - Fukada, Atsuki; Yasui, Hideki; Uto, Tomoaki; Suzuki, Shioto; Sato, Jun; Imokawa, Shiro; Suda, Takafumi
Abstract: An 85-year-old man who did not have any hematological or respiratory disorders was transferred to our hospital because of progressive dyspnea. Computed tomography (CT) findings showed ground-glass opacities with a centrilobular distribution and centrilobular micronodules with a "tree-in-bud" pattern. A biopsy of the lungs showed lymphocytic infiltrations in the parenchyma and these were positive for B cell markers. A diagnosis of chronic lymphocytic leukemia (CLL) was made and direct pulmonary involvement of CLL was confirmed simultaneously. One month after initiation of chemotherapy, his symptoms improved and a chest CT scan showed marked resolution. Pulmonary infiltrates of CLL should be included in the differential diagnosis when these signs are encountered on CT.